Efektivitas Media Video Animasi dan E-Book terhadap Pengetahuan Remaja dalam Penatalaksanaan Penyalahgunaan Narkoba - Winda Triana; Ary Irfan; Solihin Sayuti; Alfari Alfari (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effectiveness of animated video media and e-books on adolescent knowledge in managing drug abuse at SMPN 19 Jambi City. The method used is a quasi-experimental two-group pretest-posttest. This research was conducted at SMPN 19 Jambi City, involving 47 respondents. The sampling technique was carried out by proportional random sampling and analyzed using the paired sample t-test. The results showed that the average value of knowledge before and after being given education with animated video media and e-books increased. The average difference in knowledge before and after being given health education with animated video media is 1.3; the difference in the average value of knowledge before and after being given health education with e-book media is 1.25%; the p-value of knowledge after providing education using animated videos is 0.001, while e-books are 0.000. In conclusion, animated video media and e-books effectively increase adolescent knowledge in managing drug abuse at SMPN 19 Jambi City. Keywords: E-Book, Knowledge, Youth, Animated Video